Penanganan Hipoperfusi Pascaoperasi Esophagectomy Gastric Pull Up dengan AKI dan Malnutrisi - Prasetyo, Eko Budi; Aditianingsih, Dita; George, Yohanes WH (Perdatin Pusat, 2014)
Pasien bedah dengan risiko tinggi adalah mereka yang menjalani pembedahan dengan resiko tinggi untuk morbiditas dan mortalitas dengan angka kejadian mortalitas lebih besar dari 5% karena adanya penyakit penyerta atau derajat pembedahan. Penelitian terakhir di Inggris menunjukan bahwa pasien yang menjalani pembedahan beresiko tinggi mencakup 12,5 % dari jumlah total pasien yang masuk ke rumah sakit tetapi lebih dari 80% kematian, dengan kurang dari 15% dari mereka yang masuk ke Intensive Care Unit (ICU) paskaoperasi. Berikut ini adalah sebuah laporan kasus dari seorang laki-laki berusia 75 tahun yang menjalani esofagektomi gastric pull up yang disebabkan oleh kanker esophagus. Sebelum operasi, pasien mengalami malnutrisi berat dan hipoalbumin. Pasien mengalami komplikasi yang mencakup hipoperfusi, cedera ginjal akut dan pneumonia di ICU. Berfokus pada penatalaksanaan hipoperfusi, pasien menjalani hemodinamik goal directed therapy dengan target metabolik akhir yaitu normalisasi laktat, ScV02 dan tingkat PC02 gap. Pasien dipindahkan ke ruang rawat dalam keadaan baik pada hari ke-9. Kata Kunci: Esofagektomi, haemodynamic goal directed therapy, hipoperfusi, pasien bedah resiko tinggi Hypoperfusion Management Post Esophagoscopy Gastric Pull Up with Acute Kidney Injury and Malnutrition High-risk surgical patient is defined as a patient, undergoing surgery, who is at a high risk for morbidity and mortality with an expected mortality greater than 5% due to the coexisting diseases and/or the severity of surgery. A recent study in the United Kingdom demonstrated that patients undergoing high-risk general surgical procedures comprised only 12.5% of surgical admissions to hospitals but over 80% of deaths, with less than 15% of these high-risk patients admitted to the ICU postoperatively. This is a case report of 75 years old male who underwent esophagectomy gastric pull up due to esophageal cancer. Preoperatively patient suffered from severe malnutrition and hypoalbuminemia. In the ICU, patient some complications such as hypoperfusion, acute kidney injury and pneumonia. Focusing on hypoperfusion management, patient was treated using haemodynamic goal-directed therapy with end point metabolic target of normalize Lactate, ScVO2 and PCO2 gap levels. Patient was transferred to the ward in good condition on the 9th day. Key words: Esophagectomy, haemodynamic goal-directed therapy, high-risk surgical patient, hypoperfusion Lee N, Hamilton M, Rhodes A.Goal-directed therapy in high risk surgical patients : clinical review. Crit Care. 2009;13:231. Pearse RM, Harrison DA, James P. Identification and characterization of the high-risk surgical population in the United Kingdom. : research. Crit Care. 2006;10:R81 Boyd O, Jackson N. How is risk defined in high-risk surgical patient management? clinical review. Crit Care. 2005;9:390–6. Kirov MY, Kuzkov VV, Molnar Z. Perioperative haemodynamic therapy. Current opinion in Crit Care. 2010;16:384–92. Park DP, Welch CA, Harrison DA. Outcomes following oesophagectomy in patients with oesophageal cancer: a secondary analysis is the ICNARC case mix programme database. Crit Care. 2009;13(Suppl 2). Absi A, Adelstein DJ, Rice T. Esophageal cancer. Cleveland clinic. 2010 Agu. Wikipedia.org [internet]. Esophagectomy [diperbaharui 2014 Jan 29]. Tersedia dari:http://en.wikipedia.org Finks JF, Osborne NH, Birkmeyer JD. Trends in hospital volume and operative mortality for high-risk surgery. N Engl J Med. 2011;364:2128–37. Dalfino L, Giglio MT, Puntillo F.Hemodynamic goal-directed therapy and post operative infections: earlier is better. A systematic review and meta-analysis.Crit Care. 2011;15:R154. Pearse RM, Rhodes A, Grounds RM. How to optimize management of high-risk surgical patients: clinical review. Crit Care. 2004;8:503–7. Isabel M, Correia D, Waitzberg D. The impact of malnutrition on morbidity, mortality, length of hospital stay and cost evaluated through multivariate model analysis. Clinical Nutrition. 2003;22 (3):235–9. Ramanathan TS, Moppeti IK, Wenn R. POSSUM scoring for patients with fractured neck of femur. BJA. 2005;94(4):430–3. Riskprediction.org.uk [internet]. Risk prediction in surgery, Dalam; c1998–2003[diperbaharui 2010 Apr].Tersedia dari: http://www.riskprediction.org.uk Vincent JL, Moreno R. Clinical review: Scoring systems in the critically ill. Crit Care. 2010;14:207Hicereti licaescremum at, es arem dum ili sero, acibuturs culi iam faude nonocupimum stiam, Ti. Ipio egerbi patum sendum dem, quostis fec in tus vivit. Grat, puliacii conum more perit, simis fatquempor losuliisquam demena, nenatumusum stractortea me etortent? quod medetis.